Conceptual framework for lean construction ambidexterity in project-based organizations. Issue 10 (3rd October 2021) - Fang, Yanqing; Daniel, Emmanuel Itodo; Li, Shuquan
Abstract: Lean construction (LC) is widely used to eliminate waste in the construction industry. However, few studies have focussed on LC capabilities. In the absence of a theoretical foundation, the equal treatment of inherent rigidity and flexibility has received little attention. This critical literature review answered the following research questions: What is the current understanding of the two characteristics of LC? Is there a theoretical explanation for their relationship ? How can LC capabilities be realized in a project-based organization? The results revealed the lack of a clear definition of LC capabilities. The study posits that LC capabilities involve ambidexterity. Ambidexterity embodies the LC philosophy, principles, and methods, with a focus on resolving the paradoxical tensions in LC projects. Ambidexterity was found to be a two-dimensional paradox comprising exploitative and exploratory capabilities. It emphasizes the achievement of a balance between the two capabilities. The proposed model indicates that LC project-based organizations provide the ideal context for the development of ambidexterity. This study uses a paradoxical lens to introduce the notion of LC capabilities as ambidexterity. This research contributes to the current knowledge and future applications of organizational ambidexterity theory to LC capability development. In addition, it will enable practitioners to understand and manage the paradoxical tensions in LC projects. The proposed framework can guide the creation of an ideal LC project-organization environment.